2020
DOI: 10.1016/j.ijporl.2020.110318
|View full text |Cite
|
Sign up to set email alerts
|

Speech pathology telepractice for children with cleft palate in the times of COVID-19 pandemic

Abstract: Objective To study whether providing Speech and Language Pathology (SLP) interventions by telepractice (TP) could effectively improve speech performance in children with cleft palate (CCP). Methods Forty-three CCP were treated with TP intervention in 45 min sessions, 2 times per week for a period of one month. Children ages ranged 4–12 years (X = 7.04; SD = 2.59). All children presented with velopharyngeal insufficiency (VPI) and compensatory articulation (CA) after pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
(44 reference statements)
2
22
1
2
Order By: Relevance
“…Recent studies have discussed the potential negative impact of COVID-19 for children and families receiving speech-language services (Tohidast et al, 2020) as well as the accelerated emergence of telepractice service delivery within the field of speech-language pathology (del Carmen Pamplona & Ysunza, 2020;Fong et al, 2020). Within this context, it is key to understand the experiences of speechlanguage pathologists (SLPs), specifically, school-based SLPs, who were supporting students remotely immediately following the school closures.…”
Section: Impact On Speech-language Pathologistsmentioning
confidence: 99%
“…Recent studies have discussed the potential negative impact of COVID-19 for children and families receiving speech-language services (Tohidast et al, 2020) as well as the accelerated emergence of telepractice service delivery within the field of speech-language pathology (del Carmen Pamplona & Ysunza, 2020;Fong et al, 2020). Within this context, it is key to understand the experiences of speechlanguage pathologists (SLPs), specifically, school-based SLPs, who were supporting students remotely immediately following the school closures.…”
Section: Impact On Speech-language Pathologistsmentioning
confidence: 99%
“…According to Klintö et al (2011), word naming is the most important speech material for speech judgement of children with cleft palate. Besides, del Carmen Pamplona and Ysunza (2020) pointed out the telepractice of speech and language pathology could improve the Ly Thi Bac LA, Nga Thi Thu NGUYEN, Anh Thi Thuy TRUONG, Thu-Giang TRAN, The-Thang NGUYEN. A bibliometric analysis of cohesive speech research of preschoolers from 1970 to 2020 speech performance of children with cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…Within this knowledge base, there was a research related to the COVID-19 pandemic. Pamplona and Ysunza (2020) showed that telepractice could be a safe tool to improve the speech performance of children with cleft palate. They also recommended alternate modes of health care services should be studied and adapted in this context.…”
Section: Figurementioning
confidence: 99%
“…Dennoch konnte gezeigt werden, dass Teletherapie auch bei sprachtherapeutischen Interventionen eine effektive Maßnahme sein kann [27]. Darüber hinaus wurde sie als ein probates Mittel zur Verbesserung des Zugangs zur Versorgung, insbesondere bei Kindern mit Sprach-und Hörstörungen, angesehen [28,29] [31]. Dennoch müssen auch die Limitationen der Teletherapie bedacht werden.…”
Section: Diskussionunclassified